SİSPLATİN NEFROTOKSİSİTESİ OLUŞTURULAN RATLARDA EPİGALLOKATEŞİN GALLATIN ETKİLERİNİN ARAŞTIRILMASI - TİMURKAAN, MUSTAFA (Fırat Üniveristesi, 2010)
Sisplatin (CDDP) nefrotoksisitesi böbrekte oksidatif strese neden olur ve CDDP'nin klinik kullanımını kısıtlar. Epigallokateşin gallat (EGCG) yeşil çaydan derive edilen güçlü bir antioksidandır. Bu çalışmada; CDDP'nin neden olduğu nefrotoksite ve lipid peroksidasyonuna EGCG'nin etkisi deneysel olarak araştırıldı.Çalışmada, 4 gruba (n=7) ayrılarak toplam 28 adet erkek Wistar rat kullanıldı. (i) Kontrol grubu, (ii) EGCG (100 mg/kg/gün) grubu, (iii) CDDP verilen CDDP (7 mg/kg i.p, tek doz), (iv) EGCG (100 mg/kg/gün)+CDDP grubu (7 mg/kg i.p., tek doz). CDDP uygulaması serum üre nitrojeni ve kreatininde belirgin bir artışa neden oldu (p<0.001). Serum üre nitrojeni ve kreatinin düzeyleri EGCG+CDDP grubunda CDDP grubuna göre daha düşüktü (p<0.001). CDDP verilen ratlarda serum malondialdehid (MDA) düzeylerinde belirgin artış gözlendi (p<0.05). EGCG, MDA'daki artışı önledi (p<0.05). Renal Bax protein ekspresyonu CDDP grubunda kontrol grubuna göre daha yüksekti, EGCG tedavisi ile Bax düzeylerinde anlamlı azalma oldu (p<0.05). Bcl-2 protein ekspresyonu EGCG+CDDP grubunda CDDP grubuna göre daha yüksekti (p<0.05). Böbrek dokusunda Hsp60 ve Hsp70 ekspresyonu yalnız CDDP verilen ratlara göre, CDDP ile birlikte EGCG verilen ratlarda daha düşüktü (p<0.001). CDDP`nin neden olduğu renal histopatolojik değişiklikler EGCG tedavisi ile belirgin ölçüde düzeldi.Bu sonuçlar CDDP'nin oksidatif strese ve böbrek hasarına neden olduğunu gösterir. EGCG tedavisi oksidatif stresi azaltarak ve Bax/Bcl-2 protein ekspresyonlarını etkileyerek sisplatin nefrotoksisitenin önlenmesinde terapötik rol oynayabilir.Anahtar Kelimeler: sisplatin, nefrotoksisite, EGCG, MDA, Bax/Bcl-2, Hsp60-70

Cisplatin (CDDP)-induced nephrotoxicity is related to an increase in oxidative stress in the kidney and limits clinical use of CDDP. Epigallocatechin gallate (EGCG), a very potent antioxidant derived from green tea. In the present study, we investigated the effect of EGCG against CDDP-induced lipid peroxidation and nephrotoxicity in rats.Male wistar rats (n=28, 8 wk-old, between 200-215 g) were divided into four groups: (i) control rats, (ii) EGCG (100 mgkg-1, daily)-control rats, (iii) CDDP-injected rats, CDDP group (7 mgkg?1 i.p, single dose) (iv) EGCG-treated (100 mgkg?1, daily) CDDP-injected rats (EGCG+CDDP group). CDDP administration resulted in significant increase in serum urea nitrogen and creatinine (p<0.001). Serum creatinine and urea nitrogen levels were lower in rats treated with EGCG+CDDP compared with rats treated with CDDP alone (p<0.001). The serum from the CDDP-treated rats showed a significant increase in malondialdehyde (MDA) levels in comparison to the values (p<0.05). EGCG prevented the rise of MDA (p<0.05). Renal Bax protein expression was significantly higher in CDDP-treated rats compared with control rats, and EGCG treatment significantly reduced the levels of Bax (p<0.05). Bcl?2 protein expression was higher in EGCG+CDDP administered rats than CDDP-injected rats (p<0.05). The expression of renal Hsp60 and Hsp70 was significantly lower in EGCG+CDDP group compared with rats treated with CDDP alone (p<0.001). CDDP-induced renal histopathological changes were significantly improved with EGCG.These results show that CDDP produces oxidative stress and renal damage. In conclusion, our study show that EGCG, which reduces oxidative stress and changes the expression of Bax and Bcl-2 protein, has signi ? cant potential as a therapeutic intervention for CDDP-induced renal injury.Key words: cisplatin, nephrotoxicity, EGCG, MDA, Bax/bcl-2, Hsp60-70
The investigation of the effects of epigallocatechin gallate (EGCG) in cisplatin-induced nephrotoxicity in rats
Keywords: Nefroloji